Florid Papillomatosis (Adenoma) and other Benign Tumours of the Nipple and Areola - Doctor, Vatsala M. (Nature Publishing Group, 1971)
The paper deals with 20 benign tumours of the nipple and areola. The most common lesion was adenoma or florid papillomatosis (11 cases). On the basis of clinical and histological differences, the cases were divided into two groups. Group I.—Tumours showing an adenomatous pattern (5 cases) appropriately termed adenoma of the nipple. Chief clinical features were younger age, long duration and enlargement of the nipple as a predominant symptom. Histological characteristics were elongated tubules separated by a varying amount of fibrous stroma and squamous metaplasia in some of the cases. Group II.—Tumours showing a papillomatous pattern (6 cases) appropriately designated as florid papillomatosis. Clinically, the patients were older. Chief complaint was bleeding from the nipple of a few months' duration. Histologically, dilated lactiferous ducts were seen filled with papillary, cribriform and solid growth of cells. Other features such as apocrine metaplasia, foam cells and central necrosis were observed. The interpretation of this grouping is discussed. A case of adenoma of an accessory nipple is reported. Other benign tumours observed were five papillomas, one leiomyoma, one haemangioma, one fibroma and one lipoma. IMAGES: